Job search behavior of unemployed in Russia - Natalia Smirnova (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
This paper explores the determinants of job search behavior, search intensity and choices of search methods of the unemployed workers in transitional Russia.We use pooled data from rounds 5-9 of the Russia Longitudinal Monitoring Survey (RLMS) to estimate the effects of socio-economic factors on the choices workers make while looking for a job.The results show that women are significantly less likely than men to engage in job searches, lag significantly behind men in search intensity, and significantly differ from men in their search strategies.The job search behavior of workers living in metropolitan areas of Moscow and St.Petersburg differs substantially from the behavior of workers living elsewhere in Russia.The most frequently used search strategy in Russia, as in other countries, is contacting friends and relatives for job leads.
URN:NBN:fi:bof-201408072096
Keywords: J64; P23; 330; Russia; Transition; Job Search; Search Intensity; logit